Penerapan Problem Based Learning untuk Meningkatkan Pemahaman Materi Magnet Di Kelas V SD Supriyadi Semarang - Zakiyyah, Lutfi; Mudzanatun, Mudzanatun; Setyaningsih, Ariani Nur (Peneliti.net, 2024)
The aim of this research is to increase students understanding of magnetic material through the Problem Based Learning (PBL) learning mode. This research is Classroom Action Research (PTK) which has two cycles. Each cycle has four stages, namely planning, implementation, observation, and reflection. The data collection techniques used are interviews, observation, tests and documentation. Based on the research results, it shows that the application of the Problem Based Learning (PBL) learning model can improve understanding of magnetic material in class V students at SD Supriyadi Semarang.